Pressure retarded osmosis for osmotic power production: influence of internal concentration polarization and membrane fouling - She, Qianhong (2014)
Pressure retarded osmosis (PRO) has attracted increasing interest in recent years due to its potential for harvesting the renewable and sustainable osmotic energy from the mixing of two water streams with different salinities. However, the performance of PRO process is strongly affected by the internal concentration polarization (ICP) and membrane fouling. This study characterized ICP and fouling in PRO processes by varying the operating conditions (such as draw and feed solution concentration and composition, membrane types, membrane orientation, temperature, and feed spacer geometry). The phenomenon of reverse solute diffusion from draw solution to feed solution and its adverse effect on ICP, fouling, and PRO performance were also investigated. The commercial cellulose triacetate (CTA) forward osmosis (FO) membranes were used in all the PRO experiments and the alginate was selected as a model foulant to study membrane fouling.